ANALISIS DAMPAK MASUKNYA TEKNOLOGI CANGGIH DI USAHA DAGANG KERUPUK SENO TERHADAP PENYERAPAN TENAGA KERJA DI KECAMATAN MANTUP - Ratna Handayati; Henny Mahmudah (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2019)
This study aims to analyze the negative and positive impacts due to the inclusion of advanced technology in Seno cracker trading business in the District of Mantup, Lamongan Regency. This research using quantitative descriptive method, while collecting data by interviewing and submitting a questionnaire to the employees of the Seno cracker trading business. The population in this study were all employees. While the sample is determined by the census method, which is data collection that includes all elements or members of the population under investigation. From the results of a simple regression analysis, it is known that the influence of technological progress on the workforce, while the rest is influenced by other factors outside the independent factor under study. From the results of these tests, it can be concluded that the factor of technological progress has an influence on labor in the commercial business.